The Engineering Properties and Geochemical Relationship For The Volcaniclastic Rocks Of The Muqdadiya Formation In Hemrin Area, NE. IRAQ - Hassan , Shatha Fathi; Ahmad , Walid Abd ALmajeed; Hussien , Ayad Ali (Iraqi Journal of Science, 2022)
Volcaniclastic rocks of Al Muqdadiya Formation (Pliocene) in Injana area, southern Hemrin anticline, NE of Iraq, were studied ( petrographically, physically, mineralogically and geochemically , as well as the engineering properties) to assess the suitability of volcaniclastic rocks to use them in industry as refractories. The results show that the physical and engineering properties change with the temperature change. The bulk density and the specific gravity increase by increasing temperature while the apparent porosity, water sorption and the linear shrinkage decrease. On the other hand the compressive strength increase by increasing temperature. The volcaniclastics have very low thermal conductivity.The petrography, mineralogy and geochemistry of these rocks show that there are positive and negative correlations between the major oxides as well as the minerals that make it suitable for refractory industry.